CORNERSTONES COMMUNITY PARTNERHIPS (USA) ASSISTS COMMUNITIES IN PRESERVING THEIR EARTHEN ARCHITECTURAL HERITAGE - Barrow, Jake; Jones, Robin (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
In 2011, Cornerstones Community Partnerships celebrated 25 years of outreach: disseminating information and educating Southwest communities about the regional heritage of earthen architecture. Cornerstones began when a conditions survey of over 300 adobe churches, missions, and moradas took place, resulting in the 1986 formation of Churches: Symbols of Community, whose mission was to strengthen communities by assisting in their preservation of historic buildings and cultural traditions. In 1994, Churches became Cornerstones Community Partnerships, a non-proit corporation. Initially, work focused in northern New Mexico, home to a unique patrimony of vernacular-earthen architecture; Cornerstones has now built a national and international reputation for the creative use of historic preservation as a tool for community revitalization, the afirmation of cultural values, and the training of youth in traditional-building skills and sustainable-construction methods. The largest aspect of this work has been the dissemination of skills and methodologies used for centuries to maintain and perpetuate earthen architecture. Cornerstones’ goal has been to educate communities and others about the beneits of traditional building, while also taking into account the very real situations of each work site and community. To this end, different strategies are employed concerning community volunteerism and outcomes. These strategies have also pushed Cornerstones’ staff to develop new outreach materials and partnerships. An examination of past and present projects (Pajarito, Socorro, San Miguel, and Santo Domingo) demonstrates these processes of education, strategies, and developments, and the paper concludes with a commentary about the future.